Respuesta :

Answer:

hope it helps forget about my writing

Ver imagen Mayuk68

Answer:

(-1.43, -5.57)

Step-by-step explanation:

Elimination:

First we need to line up x or y to be the opposite so they can be eliminated:

4x - 3y = 11

-2( 2x - 5y = 25) which is

-4x + 10y = -50

Next step we cancel out the x but adding both equations which would isolate the y:

7y = -39

y = -5.57

After finding y, plug it back into the equation to find x:

4x - 3(-5.57) = 11

4x + 16.71 = 11

4x = -5.71

x = -1.43

To ensure it is correct, we can plug it back into both equations:

4(-1.43) - 3(-5.57) = 11

2(-1.43) - 5(-5.57) = 25

ACCESS MORE